The multifaceted impact of physical exercise on FoxO signaling pathways - Liu, Wei; Meng, Pengjun; Li, Zhi; Shen, Yifei; Meng, Xin; Jin, Shen; Hu, Mengdi (Frontiers in Cell and Developmental Biology, 2025)
This review explores the multifaceted impact of physical exercise on FoxO signaling pathways, which play a central role in cellular homeostasis, stress response, metabolism, and longevity. Exercise influences FoxO proteins—particularly FoxO1, FoxO3, FoxO4, and FoxO6—through diverse mechanisms, including phosphorylation, acetylation, and ubiquitination, determining their localization, transcriptional activity, and stability. Regular exercise modulates FoxO signaling by activating pathways like PI3K/AKT, AMPK, SIRT1, and IGF-1, promoting cellular resilience against oxidative stress, apoptosis, and metabolic dysfunction. The review highlights how exercise-induced modulation of FoxO pathways contributes to improved insulin sensitivity, muscle hypertrophy, cardiovascular health, neuroprotection, and reduced risks of chronic diseases, including metabolic syndrome, neurodegeneration, cardiovascular disease, and cancer. Additionally, it addresses the role of exercise in preventing muscle atrophy under various conditions, such as pharmacological interventions, aging, disease, and dietary factors. By enhancing FoxO signaling, exercise promotes anabolic processes, mitochondrial function, autophagy, and antioxidant defenses. Understanding the intricate relationship between exercise and FoxO pathways offers insights into developing therapeutic strategies to mitigate disease progression.